Much Ado about Nothing: Turning The Global Compact into a Red Herring in Italy and Europe (Politeja, 2019)
The Global Compact for Safe, Orderly and Regular Migration is, as The Economist described it in a recent column by Tom Nuttall, a dull piece of reading. At best, stressed Nuttal, it helps build the trust between sending and receiving countries that is the foundation of any meaningful international policy.Then how did a non-binding, declaratory intergovernmental agreement becamea crucial part of the political discourse in a considerable number of EU countries, effectively leading to the withdrawal of several governments from the Compact? The upheaval caused by the adoption of the Compact (which hadalready been discussed and agreed upon by all signatory governments in July, before becoming a token for nationalist propaganda) has once again demonstrated the inability of the EU to grow towards a sensitive migration policy, and the recklessness of many governments in refusing to engage in a reasonable conversation with other international actors in favour of a political line led by sensationalism and misinformation. The aim of this research paper is to map thedevelopment of the debate over the Global Compact in Italy building up to its abstention during the Marrakesh Conference on December 10th-11th. The research focuses on the main actors of the current political discourse in Italy, their inaccuracy and deliberate ambiguity in addressing concerns over the Compactduring Parliamentary sessions and through the mass media, and the failure of the opposition, together with civil society, to leverage a valid counterargument to the growing hysteria about the migration crisis. The expected outcomes are the identification of common patterns in the nationalist discourse in Italy and the advancement of possible new practices to effectively foster a consistent, level-headed conversation about migration management that steers away from sterile symbolism and responsibly addresses community issues at the national and EU levels.